2013
DOI: 10.1093/humupd/dmt033
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between gut and adipose hormones, and reproduction

Abstract: Gut and adipose hormones interact with the reproductive axis as well as with each other. While leptin and insulin have stimulatory effects and ghrelin has inhibitory effects on hypothalamic GnRH secretion, there is increasing evidence for their roles in other sites of the reproductive axis as well as evidence for the roles of other gut and adipose hormones in the complex interplay between nutrition and reproduction. As our understanding improves, so will our ability to identify and design novel therapeutic opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 290 publications
(307 reference statements)
2
106
0
3
Order By: Relevance
“…Poor body condition can also reduce the amount of substrate that a female can mobilize from her body to synthesize milk (Berry et al, 2007) and/or reduce the condition of skeletal muscle and other organs that are necessary to capture prey for dependent young (Bachman, 1993). Physiological indicators of body condition, such as the levels of the adipose and gastrointestinal hormones leptin and ghrelin, appear to play an important role in permitting or inhibiting ovulation (Comninos et al, 2014), and thus could reduce future reproductive fitness. Finally, both correlational and experimental studies have shown that reproduction can reduce immune function, which is predicted to reduce the probability of survival (Cichońet al, 2001;Kortet et al, 2003;Lozano and Lank, 2003;Ardia, 2005).…”
Section: Loss Of Somatic Storesmentioning
confidence: 99%
“…Poor body condition can also reduce the amount of substrate that a female can mobilize from her body to synthesize milk (Berry et al, 2007) and/or reduce the condition of skeletal muscle and other organs that are necessary to capture prey for dependent young (Bachman, 1993). Physiological indicators of body condition, such as the levels of the adipose and gastrointestinal hormones leptin and ghrelin, appear to play an important role in permitting or inhibiting ovulation (Comninos et al, 2014), and thus could reduce future reproductive fitness. Finally, both correlational and experimental studies have shown that reproduction can reduce immune function, which is predicted to reduce the probability of survival (Cichońet al, 2001;Kortet et al, 2003;Lozano and Lank, 2003;Ardia, 2005).…”
Section: Loss Of Somatic Storesmentioning
confidence: 99%
“…In females, the Molluscan insulin-related peptide 5 [Genbank:CU987248] was more expressed in Danish progeny. In mammals, the role of insulin pathway in fertility is well known [65] and in fish the insulin pathway has been positively associated to gamete quality [66]. In C. gigas, an Insulin-related peptide receptor has previously been identified in oysters by Gricourt et al [67] as well as several factors of the insulin signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to mice, people treated with exogenous leptin were hyperphagic and hyperinsulinemic [5]. Also, excessive leptin secretion was related to infertility in obese women [6].…”
Section: Introductionmentioning
confidence: 92%